Dominasi Platform Digital dan Tantangan Penegakan Hukum terhadap Praktik Anti Kompetisi dalam Ekonomi Berbasis Data - Ardiansyah Putra Mahendra; Naufal Rizky Ramadhan (Universitas Sains dan Teknologi Komputer, 2026)
The rapid growth of the data-driven economy has intensified the dominance of digital platforms, creating challenges for market competition and legal enforcement. Large technology companies increasingly control market access and user data, leading to structural imbalances and potential anti-competitive behavior. This study aims to develop a comprehensive measurement of platform dominance through the Platform Dominance Legal Index (PDLI), integrating market share and data control to better capture digital market power. The research adopts a normative juridical approach combined with quantitative analysis using secondary data from academic literature, industry reports, and regulatory documents. Market concentration is measured by the Herfindahl–Hirschman Index (HHI), while PDLI assesses dominance using economic and data-related indicators. The results show a highly concentrated market, with an HHI value of 2530, indicating strong oligopolistic conditions. Google recorded the highest PDLI score of 35.88, followed by Amazon at 18.48 and Meta at 15.30, indicating clear differences in dominance levels. The findings also indicate that platforms with strong data control maintain significant dominance even with a lower market share. Practices such as self-preferencing, predatory pricing, and lock-in effects are associated with higher levels of dominance. The study provides a structured framework for assessing digital platform dominance and supports regulators in developing more adaptive competition policies.